2016
DOI: 10.1080/1354750x.2016.1217934
|View full text |Cite
|
Sign up to set email alerts
|

Micronuclei as a marker for medical screening of subjects continuously occupationally exposed to low doses of ionizing radiation

Abstract: The obtained data encourage us to consider MN as valuable markers for preventive medical screening of occupationally exposed groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
3
0
3
Order By: Relevance
“…Additionally, among the 32 MN studies, 23 evaluated the relationship (correlation or dose-response) between IR exposure and MN frequencies using two alternative indicators of exposure (using one or both indicators): cumulative dose from personal dosimeters (14 studies) and/or duration of exposure in years (16 studies). Among those, a significant association/correlation between cumulative dose or duration of exposure and MN frequencies were reported in 5/14 and 9/16 studies, respectively [ 23 , 32 , 38 , 61 , 64 , 65 , 74 , 77 , 82 ]. Additionally, in professionals working in a nuclear medicine department, both MN and SCE levels were significantly higher during their occupational exposure compared to levels immediately after vacation period [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, among the 32 MN studies, 23 evaluated the relationship (correlation or dose-response) between IR exposure and MN frequencies using two alternative indicators of exposure (using one or both indicators): cumulative dose from personal dosimeters (14 studies) and/or duration of exposure in years (16 studies). Among those, a significant association/correlation between cumulative dose or duration of exposure and MN frequencies were reported in 5/14 and 9/16 studies, respectively [ 23 , 32 , 38 , 61 , 64 , 65 , 74 , 77 , 82 ]. Additionally, in professionals working in a nuclear medicine department, both MN and SCE levels were significantly higher during their occupational exposure compared to levels immediately after vacation period [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of NPB frequencies, four studies reported a lack of a significant difference between IR-exposed and unexposed workers [ 24 , 45 , 61 , 69 ], and three studies showed significantly elevated NPB frequencies in IR-exposed medical workers compared to controls [ 33 , 58 , 65 ]. Meta-analysis carried out on the data from six studies with complete information ( Figure 6 ) reported a significant overall difference in NPB frequencies between IR exposed and unexposed workers (θpooled = 2.32; 95% CI 1.10–3.54; Z = 3.72, p < 10 −3 ; I 2 = 97.87%; Q = 234.19, p < 10 −3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1 Ensayo de micronúcleos en la evaluación de la genotoxicidad de las radiaciones ionizantes El daño radioinducido al material genético puede ser registrado mediante distintos ensayos con biomarcadores citogenéticos, los cuales constituyen una herramienta auxiliar en la protección radiológica y un instrumento fundamental en el biomonitoreo de poblaciones expuestas a RI (Pajic et al, 2017).…”
Section: Referente Teóricounclassified
“…El MNBC ha sido muy reconocido en el biomonitoreo de individuos expuestos a RI, pues esta es capaz de infligir daño sobre el ADN, lo que conlleva un riesgo de salud a corto y largo plazo. La vigilancia de tal factor genotóxico en el personal ocupacionalmente expuesto (POE) contribuye a adoptar medidas preventivas de radioprotección y de buenas prácticas radiológicas; en ese sentido, el MNBC constituye un valioso biomarcador de efecto temprano en esquemas de salud ocupacional del POE (Pajic et al, 2017).…”
Section: Introductionunclassified